The Contribution of African Women to Economic Growth and Development in Post-Colonial Africa : Historical Perspectives and Policy Implications - Akyeampong, Emmanuel (World Bank, Washington, DC, 2013)
This paper draws on history, anthropology, and economics to examine the dynamics and extent of women's contribution to growth and economic development in post-colonial Africa. The paper investigates the paradox of increased female enrollment in education and the persistence of gender discrimination in labor force participation; it also considers the overwhelming importance of the informal economy in female economic activity. The first axis the paper studies is whether reducing educational gender gaps enhances growth in per capita gross domestic product and reduces female fertility rates and infant mortality. The question is, why would some African countries resist this pattern? The second axis examines agriculture and home production. Women's economic activities in the informal economy largely represent the commercialization of domestic skills and dependence on social networks. The shunting of female production to the informal sector in the male-dominated colonial economy is easy to understand, but why has the informal economy persisted where female production is concerned well beyond the colonial period? The paper attempts to explain these trajectories by using country case studies on Senegal, Botswana, and Kenya. Although women's contribution to growth and economic development seems to be positive and significant in predominantly Christian and mineral-rich economies, it is more constrained in pronounced Muslim dominated countries and agrarian economies. At the same time, impressive uniform growth in informal sector production in recent years suggests that occupational job segregation and gender inequality remain strong across the region, despite the apparent loosening of traditional norms and cultural beliefs, most notably illustrated by the reduction in educational gender gaps and increased female labor force participation rates.